Ο Αύγουστος στο πλαίσιο της πολιτικής του Μουσολίνι - Αρταβάνη, Ιουλία (Peri Istorias, 2022)
The current article considers the particular significance of the first Roman emperor Augustus in the political propaganda of the fascist regime, as a role model for Mussolini, via the promotion of certain Roman antiquities.